THE WEIGHT OF FERTILITY: A COMPREHENSIVE STUDY ON THE IMPACT OF OVERWEIGHT AND OBESITY ON MALE RE-PRODUCTIVE HORMONES AND SPERM QUALITY - Sanjay Yatnale; Dr. Nita Sahi; Pooja Awasthi; Dr. Pankaj Kaingade (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
This research paper investigates the relationship between overweight and obesity and male fertility parameters, including sperm counts, reproductive hormone levels, sperm DNA integrity, and various biochemical markers of metabolic health. We examine the associations between obesity-related factors and male fertility outcomes, including lipid profile (total cholesterol, LDL, HDL, triglycerides), glucose metabolism (fasting glucose, insulin sensitivity), inflammatory markers (CRP, IL-6), hormones (TSH, FT4, FT3, prolactin, inhibin B), and oxidative stress markers (MDA, TAC). Our findings suggest that excess body weight is associated with alterations in these biochemical parameters, which may contribute to the decline in male fertility outcomes. The results of this study provide a comprehensive understanding of the impact of overweight and obesity on male reproductive health and may inform clinical practice and public health interventions aimed at addressing fertility issues in overweight and obese men.